2013
DOI: 10.1371/journal.pone.0066766
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Paternal and Maternal Smoking on Semen Quality of Adolescent Men

Abstract: BackgroundMaternal smoking during pregnancy has been reported to negatively impact sperm counts of the sons. Sufficient data on the effect of paternal smoking is lacking.ObjectivesWe wished to elucidate the impact of maternal and paternal smoking during pregnancy and current own smoking on reproductive function of the male offspring.MethodsSemen parameters including sperm DNA integrity were analyzed in 295 adolescents from the general population close to Malmö, Sweden, recruited for the study during 2008–2010.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 62 publications
5
45
0
1
Order By: Relevance
“…4,5,7,9,[24][25][26][27][28][29] In utero smoking exposure of fathers could influence primordial germ cell development. 3 A prepubertal vulnerability window could be related to de novo DNA methylation occurring during primordial germ cell differentiation to spermatogonia. 30 Such a window is indicated by the OR is per 2-year increase in time before birth at which smoking stopped, with the baseline category set as those who stopped within 3 years of the child's birth and a single upper category for those who stopped >15 years before the child's birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,7,9,[24][25][26][27][28][29] In utero smoking exposure of fathers could influence primordial germ cell development. 3 A prepubertal vulnerability window could be related to de novo DNA methylation occurring during primordial germ cell differentiation to spermatogonia. 30 Such a window is indicated by the OR is per 2-year increase in time before birth at which smoking stopped, with the baseline category set as those who stopped within 3 years of the child's birth and a single upper category for those who stopped >15 years before the child's birth.…”
Section: Discussionmentioning
confidence: 99%
“…1 Environmental factors such as smoking and occupational exposures can cause genetic and epigenetic changes in sperm that are transmissible to offspring. [2][3][4][5][6][7][8][9] There is evidence for inheritable effects of food restriction through the male line from human studies, suggesting particular effects on offspring when exposure occurs during prepuberty.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that paternal smoking does have implications for offspring health: reduced semen parameters have been detected in adolescents whose fathers were smokers, even though no difference was seen in the semen of the fathers [114]. In addition, the Avon Longitudinal Study of Parents and Children found that fathers who began smoking before the age of 11 years had sons with higher BMI compared to those who began smoking later in life [115].…”
Section: Smokingmentioning
confidence: 99%
“…From a previous study of reproductive function in men from the general population (Axelsson et al, 2013), we had access to maternal serum samples from early pregnancy through a Swedish screening program for rubella. Most of these samples were collected within the suggested corresponding MPW in humans, between the 8th and 14th gestational week (Welsh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%